The Impact of Electronic Commerce on China’s Energy Consumption - Chen, Weitao (Frontiers in Environmental Science, 2022)
The rapid development of e-commerce in China in recent years has transformed China’s economic and social production landscape as well as people’s lifestyles. In addition, it has an increasing impact on China’s energy consumption. Based on Melitz (2003), this paper introduces the energy efficiency parameters to propose a theoretical analysis model, and performs theoretical and empirical analysis of the impact of e-commerce on China’s energy consumption using panel data at the provincial level in China. This paper suggests that the development of e-commerce can significantly enhance China’s energy output efficiency, reduce energy consumption per unit of GDP, and curb the excessive growth of total energy consumption. Meanwhile, increased investment in energy conservation, technological progress, and optimized energy consumption structure can also help decrease China's energy consumption per unit of GDP, thus decreasing environmental pollution. Finally, this paper proposes policy suggestions to lower energy consumption per unit of GDP and control the excessive growth of China's total energy consumption. Compared with existing studies, the main contributions of this paper are as follows. First, because there are only a few studies on e-commerce and energy consumption, this paper further supplements and enriches relevant literature. Second, this paper proposes a theoretical model regarding the impact of e-commerce development on energy consumption, adding a new perspective to research. Third, there is a lack of adequate studies on the development of China’s e-commerce landscape. While using China’s e-commerce development index data at the provincial level, this paper sets up a panel data regression model and performs in-depth analysis of the impact of e-commerce development on China's energy consumption.